ANALISIS PERSEPSI DAN ATRAKSI WISATA ALTERNATIF UNTUK MENDUKUNG PENGEMBANGAN KAWASAN AIR TERJUN TIU TEJA, LOMBOK UTARA - Kornelia Webliana; Maiser Syahputra; Dwi Sukma Rini (Forestry Study Program University Of Mataram, 2018)
Tiu Teja waterfall is one of nature tourism which is currently well known by the community and get important attention from the Government of North Lombok Regency. The development of Tiu Teja Waterfall tourism is expected to support the economy of the surrounding villages by engaging in tourism activities. Implementation of research aims to analyze the market and tourist products as well as analyze the supporting attractions or alternative tourist attractions that become one unity of Destination with Tiu Teja Waterfall area. The results showed that the visit in the period of April to October 2017 is dominated by domestic tourists with the pattern of adventure tourism journey. Analysis of the components of the tourist market shows several factors that lead to dissatisfaction in the tour of the difficulty of location attainment, inadequate supporting facilities, lack of accommodation facilities, lack of trading facilities and other factors. Tourism Product Analysis describes the types of supporting attractions around the Waterfall area in the form of landscape, agrItourism, cultural and culinary tourism. Types Tourist attractions Tiu Teja supporters are then categorized into natural attractions, cultural attractions and man-madeattractions. This supporting attraction can be used as an alternative tour around the Forest Area of Santong Village. The result of this study is expected to be considered in planning development Waterfall tour as one of North Lombok tourist destination. Keywords: Tourist attraction, Tourist market, Tourist Product, Tiu Teja